Dead letters on a page? Civic agency and inclusive governance in neopatrimonialism. Issue 4 (7th June 2017) - Puljek-Shank, Randall
ABSTRACT: Neopatrimonialism has explanatory power regarding the limitations of post-war democratization because it considers the combination of formally-democratic institutions together with power relations based on patronage. Neopatrimonialism does not however explain why marginalized groups make political claims in such inhospitable climates, nor have their experiences of governance processes been adequately explored. This paper addresses this gap based on empirical research in Bosnia-Herzegovina, applying a framework of civic agency to elaborate the goals and capacities of civil society actors. Under what conditions can civic agency foster inclusive governance outcomes? The research found that perceptions of limited and ambiguous outcomes from engagement in governance processes encourage civil society organizations to have incrementalist goals and limit self-perceptions of capacity. Inclusive outcomes were nonetheless more likely with persistent intentions and actions. Transactional capacities based on ties to political actors rather than participatory capacities based on political mobilization were more likely to lead to inclusive governance outcomes.